Personal Thermal Management by Radiative Cooling and Heating - Xue, Shidong; Huang, Guanghan; Chen, Qing; Wang, Xungai; Fan, Jintu; Shou, Dahua (Nano-Micro Letters, 2024)
Maintaining thermal comfort within the human body is crucial for optimal health and overall well-being. By merely broadening the set-point of indoor temperatures, we could significantly slash energy usage in building heating, ventilation, and air-conditioning systems. In recent years, there has been a surge in advancements in personal thermal management (PTM), aiming to regulate heat and moisture transfer within our immediate surroundings, clothing, and skin. The advent of PTM is driven by the rapid development in nano/micro-materials and energy science and engineering. An emerging research area in PTM is personal radiative thermal management (PRTM), which demonstrates immense potential with its high radiative heat transfer efficiency and ease of regulation. However, it is less taken into account in traditional textiles, and there currently lies a gap in our knowledge and understanding of PRTM. In this review, we aim to present a thorough analysis of advanced textile materials and technologies for PRTM. Specifically, we will introduce and discuss the underlying radiation heat transfer mechanisms, fabrication methods of textiles, and various indoor/outdoor applications in light of their different regulation functionalities, including radiative cooling, radiative heating, and dual-mode thermoregulation. Furthermore, we will shine a light on the current hurdles, propose potential strategies, and delve into future technology trends for PRTM with an emphasis on functionalities and applications. Highlights: 1 This review delves into the intricate relationship between thermal models, function-oriented design principles, and practical applications in personal radiative thermal management (PRTM). 2 It provides an in-depth discussion on design strategies for radiative cooling, heating, and dual-mode modulating textiles, offering practical insights for application. 3 It offers a thorough examination of the prospects and challenges of PRTM textiles, proposing potential solutions and future directions for the field.